THE NATURE OF STRUCTURE-BONDED H2O IN ILLITE AND LEUCOPHYLLITE FROM DEHYDRATION AND DEHYDROXYLATION EXPERIMENTS - Drits V.A.; McCarty D.K. (My University, 2007)
Thermogravimetric analysis combined with mass spectrometry was used to study H2O bound to samples of illite-1M, illite-2M2 and leucophyllite-1M. Samples were heated in a helium atmosphere at different temperatures and after heating at each given temperature were cooled to 35°C. Each cycle in the mass 18 spectrum of each illite sample contains a low-temperature peak at 60-80°C, a medium-temperature peak at 340-360°C, and a high-temperature peak at a temperature that is very close to the maximum temperature of sample heating of a given cycle. Within each heating-cooling cycle, the sample weight at the beginning of cooling is lower than that at the end of the same cooling stage because of H2O resorption. However, the number of H2O molecules released during each medium-temperature heating cycle is equal to the number of H2O molecules resorbed during the corresponding cooling stages. The weight losses, under medium-temperature heating, of the illite samples are related to dehydration when H2O molecules located in K-free sites of the illite interlayers are removed. The medium-temperature peak is reproducible for each cycle because during each cooling stage the illite interlayers resorb the same number of H2O molecules that were lost during the preceding dehydration. Two distinct features are characteristic of leucophyllite during heating-cooling treatments. First, the number of H2O molecules resorbed during cooling is significantly greater than the number of H2O molecules lost during dehydration. Second, the medium-temperature peaks in the spectrum appear only in the last five cycles and the maximum-peak temperature is 450-460°C. These data indicate that the heating-cooling treatments are accompanied by partial rehydroxylation. This rehydroxylation occurs during each cooling stage when a small number of resorbed H2O molecules are trapped in the interlayers, although most migrate into the octahedral sheet of the 2:1 layers and reform as OH groups. The crystal chemical factors responsible for the dehydration and rehydration as well as for the rehydroxylation reactions are discussed and speculation about the origin of the low- and medium-temperature H2O losses is presented. Copyright © 2007, The Clay Minerals Society.
Keywords: DEHYDROXYLATION; ILLITE 1M; ILLITE 2M2; LEUCOPHYLLITE; THERMOGRAVIMETRIC